1997
DOI: 10.1002/(sici)1097-0142(19971215)80:12<2268::aid-cncr8>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Extracapsular invasion of lymph node metastasis is an indicator of distant metastasis and poor prognosis in patients with thyroid papillary carcinoma

Abstract: The presence of extranodal invasion in patients with thyroid papillary carcinoma is an indicator of distant metastasis and poorer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
164
3
15

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(194 citation statements)
references
References 11 publications
12
164
3
15
Order By: Relevance
“…There have been many reports of extranodal invasion, but few related to gastric cancer. It is well known that extranodal invasion is an important indicator of poor prognosis in cancers of the pharynx, larynx, thyroid, lung, and breast [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of extranodal invasion, but few related to gastric cancer. It is well known that extranodal invasion is an important indicator of poor prognosis in cancers of the pharynx, larynx, thyroid, lung, and breast [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…1 It is the most common form of papillary carcinoma, 1 comprising almost half of the papillary thyroid carcinomas reported in recent studies. [2][3][4] Most papillary microcarcinomas remain silent and have a slow clinical course, but some behave aggressively, with local recurrence [5][6][7] and early distant metastasis, 5,7 giving rise to clinically significant disease. Furthermore, a papillary microcarcinoma may occasionally be the primary lesion of a lymph node metastasis presenting clinically as a neck mass.…”
mentioning
confidence: 99%
“…Two hundred and eight As also shown in Table 1, the median follow-up was 6.2 years (0. [8][9][10][11][12][13][14][15][16][17]. At the end of follow-up, 89 patients (42.2%) were disease-free, 74 (35.1%) maintained biochemical disease, 43 (20.4%) had structural persistence, and 5 (2.4%) died from the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Lango and cols. (10) demonstrated that the impact of ENE on the risk of developing distant (22) showed that the presence of ENE is associated with the presence of distant metastases (p < 0.0001). The absence of association between ENE and distant metastasis in our study may be due to the small number of patients in whom this characteristic was analyzed.…”
Section: Discussionmentioning
confidence: 98%